Fiber optic angle sensor based on flat and concave mirror using a multimode fused coupler - Yasin, Moh; Jusoh, Zulzilawati; Rahman, Husna Abdul; Ashadi, M.D.; Harun, Sulaiman Wadi; Ahmad, Harith (INOE, 2011)
A simple fiber optic displacement sensor (FODS) is proposed and demonstrated for angle measurement. The proposed sensor utilizes a multimode fused coupler as a probe as well as a flat or concave mirror as the target. For the flat mirror, the highest sensitivity and the best resolution is obtained at 0.114 mV/° and 71 mrad, respectively; whereas the highest sensitivity and the best resolution that is attainable when the concave mirror is used are 0.40 mV/° and 2.1 mrad, respectively. The simplicity of the design, high degree of sensitivity, dynamic range and the low cost of the fabrication make it suitable for industry and research applications.